2016
DOI: 10.1158/1078-0432.ccr-15-2145
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I, First-in-Human Study of AMG 780, an Angiopoietin-1 and -2 Inhibitor, in Patients with Advanced Solid Tumors

Abstract: Purpose: To assess the toxicity, pharmacokinetics, tumor vascular response, tumor response, and pharmacodynamics of AMG 780, a mAb designed to inhibit the interaction between angiopoietin-1 and -2 and the Tie2 receptor.Experimental Design: This was a phase I dose-escalation study of patients with advanced solid tumors refractory to standard treatment without previous antiangiogenic treatment. AMG 780 was administered by intravenous infusion every 2 weeks in doses from 0.1 to 30 mg/kg. The primary endpoints wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
(79 reference statements)
1
9
0
Order By: Relevance
“…With the caveat of limitations of cross-trial comparisons, these data are similar to findings reported in clinical trials of other inhibitors of Ang1 and Ang2, where fatigue and peripheral edema were also the most common clinical toxicities (25,26). With the exception of fatigue, there were no obvious dose-related patterns in the occurrence or severity of treatment-related AEs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With the caveat of limitations of cross-trial comparisons, these data are similar to findings reported in clinical trials of other inhibitors of Ang1 and Ang2, where fatigue and peripheral edema were also the most common clinical toxicities (25,26). With the exception of fatigue, there were no obvious dose-related patterns in the occurrence or severity of treatment-related AEs.…”
Section: Discussionsupporting
confidence: 81%
“…Apart from the caveat of cross-trial comparisons, a mechanistic explanation of selective inhibition of Ang2 without Ang1 inhibition may account for the lack of proteinuria seen with nesvacumab (29)(30)(31), unlike the proteinuria grade ! 3 reported with the Ang1/Ang2 inhibitors trebananib and AMG780 (25,26), Except for one patient with vena cava thrombosis, occurring in the context of progressive retroperitoneal disease, there were no other thrombotic events. Reversible CNS abnormalities seen on MRI in 3 patients were atypical in their clinical and radiologic appearance from those seen with other antiangiogenic agents (32,33).…”
Section: Discussionmentioning
confidence: 94%
“…High blood pressure appeared to be dose dependent and predominantly driven by the systemic vanucizumab-mediated VEGF-A inhibition. Across clinical studies, the frequency of G3/4 hypertension is 9%-32% with bevacizumab monotherapy (21)(22)(23)(24)(25) but 6% for single-agent Ang-1/2 antagonists (26)(27)(28)(29)(30)(31)(32)(33). Moreover, hypertension rates with bevacizumab treatment did not increase by concurrent inhibition of the Ang/ Tie-2 signaling pathway in patients with metastatic breast cancer [39%-40% (G!3: 18%-23%) compared with 38% (G!3: 19%) without concurrent Ang/Tie-2 inhibition; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Altered glomerular permeability with leakage of large proteins into the urine appears to be a direct result of VEGF-A and Ang-2 inhibition. Proteinuria is a common side effect of bevacizumab with an overall incidence (all grades) of 20% (37) and has been reported in 14% of patients treated with agents targeting the Ang/Tie2 pathway (28). Simultaneous inhibition of VEGF-A and Ang-2 with vanucizumab did not increase the rate or grade of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation